2012
DOI: 10.1155/2012/638476
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Short of It: The Role of Telomeres in Fetal Origins of Adult Disease

Abstract: Placental insufficiency, maternal malnutrition, and other causes of intrauterine growth restriction (IUGR) can significantly affect short-term growth and long-term health. Following IUGR, there is an increased risk for cardiovascular disease and Type 2 Diabetes. The etiology of these diseases is beginning to be elucidated, and premature aging or cellular senescence through increased oxidative stress and DNA damage to telomeric ends may be initiators of these disease processes. This paper will explore the areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 105 publications
(116 reference statements)
2
23
0
1
Order By: Relevance
“…2000, Sakai, et al 2003). ROS can also impair telomerase activity, with telomere attrition being a predictive marker for cardiovascular dysfunction, metabolic syndrome and other age- and DOHaD-related pathologies (Hallows, et al 2012). It is therefore possible that an in increase in ROS levels is the initial stimulus that reprograms the ART embryo, which employs transcription factors like NFE2L2, CEBPs (Manea, et al 2014), and p53 to exert acute transcriptional responses and subsequent chromatin remodeling that persists throughout development, leading to different cell type-contextual expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…2000, Sakai, et al 2003). ROS can also impair telomerase activity, with telomere attrition being a predictive marker for cardiovascular dysfunction, metabolic syndrome and other age- and DOHaD-related pathologies (Hallows, et al 2012). It is therefore possible that an in increase in ROS levels is the initial stimulus that reprograms the ART embryo, which employs transcription factors like NFE2L2, CEBPs (Manea, et al 2014), and p53 to exert acute transcriptional responses and subsequent chromatin remodeling that persists throughout development, leading to different cell type-contextual expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Growing epidemiological evidence shows that malnutrition of pregnant women is positively associated with the development of diabetes in their offspring [31][32][33]. Results of experiments with the rat model have demonstrated that limited protein intake during pregnancy may reduce liver X receptor offspring α (LXRα) histone promoter region H3 (K9, 14) acetylation, thus silencing expression of LXRα, which in turn increases expression of its target gene 11β-HSD1…”
Section: Impacts Of Maternal Undernutrition On Metabolic Syndromementioning
confidence: 99%
“…Shorter telomeres have been reported in trophoblasts from pregnancies with preeclampsia and intrauterine growth restriction, compared to uncomplicated pregnancies [16]. Moreover, oxidative stress and DNA damage to telomeric ends, as well as decreased telomerase activity can lead to premature placental aging and these findings have been implicated in the etiology of intrauterine growth restriction [18,19].…”
Section: Introductionmentioning
confidence: 99%